The Development of E-Worksheet Using Kvisoft Flipbook Maker Software Based on Lesson Study to Improve Teacher’s Critical Thinking Ability - Erna, Maria; Elfizar, Elfizar; Dewi, Citra Ayu (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The effectivity and efficiency of the learning process is very dependent on the quality of teacher. Therefore must improve their quality by conducting various learning innovations, one of them by implementing ICT-based learning. The purpose of this study was to develop e-worksheet using kvisoft flipbook maker software based on lesson study to improve chemistry teacher’s critical thinking ability. This research used development model 4-D namely define, design, develop, and disseminate. The subject of this research was involved chemistry teachers and student of grade XI of Senior High School in Rokan Hulu, Riau, Indonesia. The draft e-worksheet was validated by experts using validation questionnaires and critical thinking ability instruments using essay tests. The data were analyzed using N-Gain formulation. Based on the result, the developed e-worksheet in chemistry material has exactly valid with score percentages 88.88% and average critical thinking ability about 60 with enough category. Therefore, it can be concluded that e-worksheets using kvisoft flipbook maker software based on lesson studies that have been developed can improve critical thinking ability of teacher and students.